Multidisciplinary management of women with pelvic organ prolapse, urinary incontinence and lower urinary tract symptoms. A clinical and psychological overview - La Rosa, Valentina; Ciebiera, Michał; Lin, Li-Te; Sleiman, Zaki; Cerentini, Tais; Lordelo, Patricia; Kahramanoglu, Ilker; Bruni, Simone; Garzon, Simone; Fichera, Michele (Menopause Review/Przegląd Menopauzalny, 2019)
Although female sexual dysfunctions are common among women with urogynecological conditions, they have not been thoroughly studied and there are still many questions without an answer. The recent evidence on sexual disorders in women with urogynecological diseases shows a quite wide spectrum of therapeutic approaches, which require the physicians to take into account not only the primary symptoms, but also all the associated factors negatively affected. It has been widely underlined that gynecological diseases are often associated with high stress and have a negative impact on quality of life and psychological well-being of women affected. For this reason, a multidisciplinary approach for the management of these diseases is highly recommended. Also in the case of urogynecological disorders, it is important to take into account psychological outcomes throughout the diagnostic and therapeutic process. In the light of these considerations, the aim of this short review is to evaluate the impact of the main urogynecological diseases and the currently available therapeutic options in order to improve quality of life and sexuality of these patients and to stress the need for a multidisciplinary approach in order to minimize the negative consequences of these diseases for the sexual well-being of women and their partners.